2018
DOI: 10.1080/15389588.2017.1422601
|View full text |Cite
|
Sign up to set email alerts
|

Safe speed limits for a safe system: The relationship between speed limit and fatal crash rate for different crash types

Abstract: The positive exponential relationship between speed limit and fatal crash rate is consistent with prior research into speed and crash risk. The results indicate that speed zones of 100 km/h or more only meet the objectives of the Safe System, with regard to fatal crashes, where all crash types except rear-end crashes are exceedingly rare, such as on a high standard restricted access highway with a safe roadside design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 6 publications
1
21
0
2
Order By: Relevance
“…Asimismo, el exceso de velocidad es la segunda causa por fallecimientos, en diferentes estudios se comprobó la relación entre velocidad y tasa de mortalidad [4][5][6][7][8][9][10][11][12][13][14][15] , especialmente en las vías rurales es dónde se circula a velocidades superiores a los 80 km/h y existe mayor concentración vehicular por la densidad poblacional 35 . No obstante, las eventos que originan los fallecimientos por AT no podemos atribuirlos a una sola causa, sino a la combinación multifactorial de variables 12 -36 .…”
Section: Discussionunclassified
“…Asimismo, el exceso de velocidad es la segunda causa por fallecimientos, en diferentes estudios se comprobó la relación entre velocidad y tasa de mortalidad [4][5][6][7][8][9][10][11][12][13][14][15] , especialmente en las vías rurales es dónde se circula a velocidades superiores a los 80 km/h y existe mayor concentración vehicular por la densidad poblacional 35 . No obstante, las eventos que originan los fallecimientos por AT no podemos atribuirlos a una sola causa, sino a la combinación multifactorial de variables 12 -36 .…”
Section: Discussionunclassified
“…Asimismo, el exceso de velocidad es la segunda causa por fallecimientos, en diferentes estudios se comprobó la relación entre velocidad y tasa de mortalidad [4][5][6][7][8][9][10][11][12][13][14][15] , especialmente en las vías rurales es dónde se circula a velocidades superiores a los 80 km/h y existe mayor concentración vehicular por la densidad poblacional 35 . No obstante, las eventos que originan los fallecimientos por AT no podemos atribuirlos a una sola causa, sino a la combinación multifactorial de variables 12 -36 .…”
Section: Discussionunclassified
“…Many meta-analyses showed that the maintenance of the speed cameras is effective in speed management, reducing fatal and serious injury crashes (11,12) and safe system (13). There are different speed camera programs in different countries, for example in Iran, the number of speed cameras on rural roads improves the safety of the roads.…”
Section: Introductionmentioning
confidence: 99%